Two new species of Cosmos section Discopoda (Coreopsideae: Asteraceae) from Jalisco, Mexico - Castro Castro, Arturo; Vargas-Amado, Georgina; Harker, Mollie; Rodríguez-Contreras, Aarón (Phytotaxa, 2013)
Recent botanical explorations in western Mexico, as part of a taxonomic revision and a phylogenetic analysis of the genus Cosmos, have resulted in the discovery of two new species. The novelties belong to Cosmos section Discopoda and are described and illustrated. Morphologically, Cosmos pseudoperfoliatus resembles C. jaliscensis, C. peucedanifolius, C. palmeri and C. scabiosoides, but differs from them in having 4–7 leaf pairs on the stem, leaves tomentose on both faces, trullate external phyllaries, yellow disk florets with 4–5 lobes, and corky-tuberculate achenes. On the other hand, Cosmos ramirezianus is morphologically similar to C. montanus, but differs by its coriaceous and pinnatisect leaves, yellow internal phyllaries, yellow disk florets with light purple lobes, and by the persistence of paleae during fruiting. Phenology, distribution and habitat are provided as well as a key for the identification of the species in Cosmos section Discopoda.